KREATIVITAS ANAK MELALUI KEGIATAN MENCETAK DENGAN BAHAN ALAM - Nabila Fauziani; Atin Fatimah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2017)
Creativity as a child’s mental process which is able to produce new product that comes from the idea, a combination of new data and information from the surrounding circumstances. Based on the results of preliminary observations, the condition of child creativity is low, children react in the same way and can not develop their imagination. researchers provide action through print activities to make the activities in the classroom more enjoyable for children. The method used in this research is a method of action research consisting of 2 cycles. Each cycle consists of several stages of planning, action and observation and reflection. In cycle I is given as many as 8 times action and in cycle II of meeting 2 research have been declared succeed with creativity success criteria reach 70%. Subjects in this study were children aged 5-6 years who are in BKB Package IQRO Serang-Banten consisting of 2 boys and 8 girls. Data collection techniques through field notes, observation, interview notes and documentation. Before the action, the observation results show a percentage of 27%. In the first cycle, children’s creativity increased by 57%, this shows an increase of 30% from pre-action to cycle I. From cycle II, the development of children has a significant increase reached 87%. in other words, the creativity of the child can be improved through the activities of printing using nature materials.